Correlation of iodine symporter expression in highly and low malignant cell lines of human breast cancer differed in their sensitivity to doxorubicin - Lukianova, N.Yu.; Andriiv, A.V.; Chekhun, V.F. (Experimental Oncology, 2016)
Aim: To investigate the relationship of sodium/iodide symporter (NIS) expression with molecular phenotype of highly and low malignant cell lines of human breast cancer (BC) with different sensitivity to doxorubicin (Dox). Materials and Methods: The cell lines used in the analysis included T47D, MCF-7, MDA-MB-231, MDA-MB-468, and MCF/Dox. NIS expression was studied by immunocytochemical method. Results: The strongest iodine symporter expression (248 ± 1.9; 272 ± 3.2 and 289 ± 2.8 points, respectively) were found in cells of highly malignant cell lines — MDA-MB-231, MDA-MB-468, and MCF-7/Dox. NIS expression was significantly weaker (< 120 points) in two BC cell lines of low malignancy (MCF-7 and T47D). In addition, the reduced sensitivity to Dox is associated with elevation of NIS expression in both high and low malignant cells. We have demonstrated correlations between NIS levels and certain indices of BC malignancy, namely proliferative activity (r = 0.51), receptor status (estrogen receptor; r = –0.47; and progesteron receptor; r = –0.47) and invasiveness (r = 0.46). Conclusions: Our data evidence that NIS expression level correlates with BC cells indices of malignancy and their sensitivity to Dox. The results obtained suggest the necessity for further studies of NIS expression in BC patients aimed at prognosing disease course and monitoring treatment efficacy with anthracyclines.